Influence of Intermediate Сonnections on Stability of Power Transmission Systems - G. E. Pospelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper considers an influence of intermediate connections to power transmission systems on their stability.